155k views
1 vote
Simplify the expression:2/3 / (4) - [1/6 - 8/6]

A. 1
B. 29/24
C. -24/17
D. 23/24


Simplify the expression:2/3 / (4) - [1/6 - 8/6] A. 1 B. 29/24 C. -24/17 D. 23/24 ​-example-1
User AntouanK
by
5.0k points

2 Answers

5 votes

Answer:

It is A 1

Explanation:

Because I did the exact same lesson as you hope it helps!!!

User Zardosht
by
5.9k points
7 votes

9514 1404 393

Answer:

A. 1

Explanation:


(2)/(3)/(-4)-\left((1)/(6)-(8)/(6)\right)\\\\=(2)/(3)\cdot(-1)/(4)-\left((1-8)/(6)\right)=(-2)/(12)-(-7)/(6)\\\\=-(1)/(6)+(7)/(6)=(-1+7)/(6)=(6)/(6)=\boxed{1}

User Iquestionshard
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.